The imortance of safe LGBTQ+ spaces citywide (The Journal of Psychology and Sociology, 2023)
This article aims to contribute to the study of urban public spaces through the lens of safety and inclusiveness, as well as to consider the relationship between the influence of these spaces on the for-mation and acceptance of sexuality or gender identity, which has not been done before in Kazakhstan. In the development of cities and ensuring comfort, an important role is assigned to the promotion of a policy of security and inclusiveness. However, social, and institutional stigma, discrimination and invis-ibility of marginalized groups lead to social exclusion, which subsequently prevents these groups from fully participating in the socio-political life of the city. Based on the quantitative study (N=300, mean age=24.9), authors considered the concept of safety, the inclusiveness of public spaces in the city in relation to LGBTQ+ and studied the characteristics and features of the formation of safe spaces. Also, authors considered the relationship of urban spaces with the process of formation, acceptance of sexual-ity and gender identity of a person.Based on the results of the study, the authors claim that safe LGBTQ+ spaces are part of the urban environment that plays a significant role in ensuring the socio-psychological well-being and comfort of LGBTQ+ people, as well as an opportunity to safely socialize in an inclusive environ-ment. The significance of the research is found in the fact that the data presented contribute to ad-dressing the issues of the formation and implementation of sexuality and gender identity through the prism of the inclusiveness and safety of the city space, which was previously little sought in Kazakhstani sociology.The article proposes practical recommendations for expanding the policy of safety and inclusiveness in the public spaces of the city, taking into account the kazakh context.Key words: safety, public space, inclusiveness, LGBTQ+, well-being, discrimination.